(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human aggression is explained in many ways by psychologists, with any given explanation depending on the particular orientation of the individual. Even within the subspecialty of social psychology, variation in viewpoints can be found, with some stressing cognitive factors, others pinpointing emotional and affective determinants, and still others dealing with aggression as a part of broader social interaction system. On one matter, however, virtually all social psychologists agree Aggression is a response to specific conditions in the environment Definitions of aggression vary widely, because the term is taken from everyday speech and is used to refer to behaviour ranging from first-degree murder to verbal insults and social snubs.